Inventarisasi Vegetasi Mangrove Di Pantai Marosi Kabupaten Sumba Barat - Ni Kade Ayu Dewi Aryani (Politeknik Pertanian Negeri Kupang, 2013)
Marosi beach is an natural mangrove in West Sumba Regency. This inventory of vegetation in Marosi beach is based on the lack of scientific data in mangrove vegetation, where its will support the sustainable forest management. The line transect was develop on line of beach to collect the data. The results showed that 10 species were classified into 9 families was found, its namely Avicennia lanata (Ridley), Rhizhopora lamarckii Montréal., Lumnitzera racemosa Willd., Aegiceras corniculatum (L.) blanco, Excoecaria agallocha L., Excoecaria indica, Heritiera littoralis, Dolichandrone spathacea (Lf), Pandanus tectorius. Parkinson ex Z., L. Cerbera manghas. The distribution on tree strata, Excoecaria agallocha L. is a species whose presence is more than 73.33%. At sapling strata Rhizhopora lamarckii Montréal., Avicennia lanata (Ridley) is a species whose presence is 53.33%, At strata seedling Rhizhopora lamarckii Montréal., whose presence is a kind of 53.33%.Key words: Inventory, mangrove, habitats.